RHS gardening school : everything you need to know to get the most from your garden - Akeroyd, Simon; Bayton, Ross; Royal Horticultural Society (Great Britain) (London : Mitchell Beazley, 2021)
Keen amateur gardeners and aspiring professionals can learn from the expertise of the RHS with this handy guide. It doesn't matter if you're an old hand at gardening or just starting out, there are always things to discover and opportunities to improve, whether it's mastering a new technique or brushing up on your botany. RHS Gardening School is the perfect guide for gardeners who want to learn. Hands-on guidance and step-by-step instructions explain topics such as pruning, pest and diseases, weed removal and caring for lawns. Expert gardeners explain the underlying principles in plain English, while clear diagrams and beautiful photographs inspire and inform. This revised edition will have a fresh new look with new illustrations and photographs and an easy-to-navigate layout making it an ideal handbook for the new gardener. Become a better, smarter, more productive gardener with this complete guide to horticulture in one handy book.
Includes bibliographical references and index.
Keywords: Gardening; gardening; Gardening